Comportamento empreendedor à luz do constructo do capital psicológico e da teoria social cognitiva, na perspectiva da agência humana - Lima, Luciano Gonçalves de (2016)
The area of entrepreneurship with the fragmented studies has inhibited some consensual aspects to explain the phenomenon of entrepreneurial behavior. The replies are sought in several subjects under the most varied aspects, but it is in psychology which is supported for the explanations in order to establish characteristics that lead to understanding the entrepreneurial behavior: need for achievement, initiative, the statement, the orientation to efficiency, systematic planning and commitment to work (McClelland, 1961). In the context of positive psychology arises the organizational behavior giving rise to the psychological capital. Thus, four important forces are formed that produces a state of psychological growth in the individual: self-efficacy, optimism, hope and resilience (Luthans, Luthans, & Luthans, 2004). Not unlike the social cognitive theory, in the perspective of human agency, the psychological capital has fundamental characteristics such as intentionality in which people form intentions that include plans and action strategies to accomplish them (anticipation). This involves more than make plans directed to the future, but to create goals for yourself predicting outcomes likely to prospective acts in order to guide and motivate the efforts in advance (Bandura, 2001). Considering the characteristic of these two theories, the general purpose of this research is to analyze the entrepreneurial behavior in light of the components of the construct of psychological capital and social cognitive theory, in the perspective of human agency. For this purpose, the phenomenological procedure as research strategy was chosen in this study. Therefore, the researcher can identify the essence of human experiences described by participants. The research emphasizes the understanding of the life story of 21 entrepreneurs, who make up the Board of Commercial and Business Association, the Council of Woman Entrepreneur and the Council Young Entrepreneur in Paranavaí city, state of Paraná, Brazil. The data collection tool was a semi-structured interview. It allows security and flexibility to the researcher to the issues of research interest are addressed while giving freedom to the interviewed to express their experiences. The interviews were recorded with the consent of the participants in order to facilitate the transcription and preserve the essence of the data. The results showed that both the need for self-realization, initiative, relationship, ability to handle adversity and family basis are striking features in all the entrepreneurs of the three survey groups. One aspect that has not been investigated in the research, but that emerged in the results of this research was the solidarity. This construct is more present in the behavior of the Board of ACIAP (Commercial and Business Association) and women entrepreneurs of CME (Council of Woman Entrepreneur) to be elected the solidarity actions as a way of giving back to society by business success that was won by them over time. How the enterprises of young entrepreneurs participating in the research are at the initial stage or phase of maturation, this construct was not relevant in the study and can touch on over time during the entrepreneurial path. This way, the actions that elect an individual with entrepreneurial behavior can be explained through the optics of these two theories that supported this research. However, the psychological capital showed greater explanation because it has among other components the construct of self-efficacy that has been the basis of human agency. It is concluded that entrepreneurs bring sufficient subsidies to exhibit beliefs of self-efficacy, optimism, hope, resilience, intentionality, anticipation, self-relativity and self-reflection that can be analyzed and explained from the perspective of both the psychological capital and human agency. The three groups of entrepreneurs have psychological capital and human agency. This leads us to believe they can be characterized by their entrepreneurial behavior and stigmatized as entrepreneur.